Quality of life in dogs with idiopathic epilepsy and their owners with an emphasis on breed—A pilot study - Hamers, Maud F. N.; Plonek, Marta; Bhatti, Sofie F. M.; Bergknut, Niklas; Diaz Espineira, M. Montserrat; Santifort, Koen M.; Mandigers, Paul J. J. (Frontiers in Veterinary Science, 2023)
Epilepsy in dogs is a common chronic and serious disorder and may have an impact on the quality of life of the owners as well as the dogs themselves. The aim of this pilot study was to investigate the QoL score of dogs suffering from idiopathic epilepsy and their owners and if possible, investigate whether a breed specific difference exists. Owners, either Dutch or Belgium, were asked to participate in a web based SurveyMonkey questionnaire. A total of 402 questionnaires representing 402 dogs with epilepsy were suitable for further analysis. Of the 402 dogs, 253 were males and 149 were females. Ninety-nine different breeds were represented. Fourteen breeds (177 dogs in total) were used to calculate breed specific scores; Australian Shepherd (n=8), Beagle (n=7), Belgian Tervueren dog (n= 9), Belgian Groenendaeler dog (n=8), Border Collie (n= 38), Chihuahua (n= 9), Dachshund (n= 13), Drentsche Patrijshond (a Dutch partridge dog) (n= 14), French Bulldog (n= 12), Golden Retriever (n= 17), Labrador Retriever (n= 18) and Rottweiler (n= 12). For the Border Collie, there was a statistically significant correlation between 'epilepsy related death', the severity of the seizures (p<0.001) and cluster seizures (p<0.001). The quality of life of the Border Collie was scored lower compared to all other dogs (p=0.02). There were three breeds that had a minimal decrease in the overall quality of life score compared to all other dogs: the Chihuahua (p=0.03), Dachshund (p=0.001) and Golden retriever (p=0.01). The score for 'caring for my epileptic dog decreases my own QoL' was high for the Border Collie, Boxer, French Bulldog and Rottweiler, but was only found to be statistically significantly higher in the Border Collie (p=0.01). Scores for the Golden Retriever (p=0.04) and Labrador (p=0.006) were lower. In conclusion, this study reports breed specific quality of life scores of dogs with epilepsy and their owners, and underlines that breed by itself, is also an important factor when managing epilepsy in dogs.